2020
DOI: 10.1038/s41598-020-74080-2
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent tumor suppressor adenomatous polyposis coli promotes Axin biomolecular condensate formation and efficient β-catenin degradation

Abstract: The tumor suppressor adenomatous polyposis coli (APC) is frequently mutated in colorectal cancers. APC and Axin are core components of a destruction complex that scaffolds GSK3β and CK1 to earmark β-catenin for proteosomal degradation. Disruption of APC results in pathologic stabilization of β-catenin and oncogenesis. However, the molecular mechanism by which APC promotes β-catenin degradation is unclear. Here, we find that the intrinsically disordered region (IDR) of APC, which contains multiple β-catenin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Nanoscale models for basal β-cat degradation have been proposed, including a radial Axin structure that complexes with a ‘ratcheting’ APC to sequester, sequentially phosphorylate and release β-cat to associate with βTrCP for ubiquitination 15 , an APC-mediated regulatory loop that tunes phosphorylation rate via dynamic degradation of Axin 42 .The present findings point toward LLPS as a mechanism to concentrate sparse clients in the cytoplasm. In vitro Axin1 polymerization has been observed to be ordered 26 ,yet others have shown that Axin1 and APC form surface tension-minimizing spherical droplets that fuse over time 43 whose existence is determined by concentration and interaction strength 10 . Our results suggest that nucleation to the centrosome is central to the formation of this molecular crucible and future studies examining the modulation of DC component properties at the centrosome promise to yield new steady-state characteristics and regulatory mechanisms of Wnt signaling dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoscale models for basal β-cat degradation have been proposed, including a radial Axin structure that complexes with a ‘ratcheting’ APC to sequester, sequentially phosphorylate and release β-cat to associate with βTrCP for ubiquitination 15 , an APC-mediated regulatory loop that tunes phosphorylation rate via dynamic degradation of Axin 42 .The present findings point toward LLPS as a mechanism to concentrate sparse clients in the cytoplasm. In vitro Axin1 polymerization has been observed to be ordered 26 ,yet others have shown that Axin1 and APC form surface tension-minimizing spherical droplets that fuse over time 43 whose existence is determined by concentration and interaction strength 10 . Our results suggest that nucleation to the centrosome is central to the formation of this molecular crucible and future studies examining the modulation of DC component properties at the centrosome promise to yield new steady-state characteristics and regulatory mechanisms of Wnt signaling dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, IDRs of APC undergoes phase separation. In colorectal cells, β‑catenin degradation and Axin puncta formation can be promoted by expressing IDR of APC 134 . Dvl is a multivalent protein interacting with other Wnt signaling proteins.…”
Section: The Role Of Llps In Oncogenic Signalingmentioning
confidence: 99%
“…[ 26 ] In line with our report, the human APC fragment (1351–2070aa) that contains multiple β‐catenin and Axin interacting sites could also undergo LLPS and promote Axin puncta formation. [ 31 ] In addition to facilitating Axin LLPS, APC is also important for GSK3β‐mediated Axin phosphorylation in the Wnt “OFF” state and promotes the Axin1‐phosphorylated LRP6 interaction upon Wnt stimulation. [ 37 ] In addition, APC can prevent β‐catenin dephosphorylation before it is ubiquitinated by β‐TrCP.…”
Section: The Function Of Apc and Dvl In The Destruction Complexmentioning
confidence: 99%
“…Current evidence indicates that APC can regulate Axin function in the formation of both the destruction complex and the signalosome. [26,[30][31][32][33] APC helps stabilization of Axin homopolymerization mediated by its DAX domain and promotes Axin1 LLPS. [34] However, in SW480 cells, a colon cancer cell line with APC mutation, Axin can still form the puncta and recruit other components of the destruction complex including GSK3β, CK1 and β-catenin, [26,35] suggesting that APC may not act as a scaffold protein to mediate the LLPS-driven assembly of the destruction complex, consistent with the previous report.…”
Section: The Function Of Apc and Dvl In The Destruction Complexmentioning
confidence: 99%